DFT computations and Experimental research for Corrosion Inhibition of Carbon Steel Surface in Salinized Media Using a Novel Derivative of 2-aryl imidazo [2,1-b] Benzothiazole - Kubba, Rehab Majed; Al-Joborry, Nada Mohammed; Al-lami, Naeemah J. (Iraqi Journal of Science, 2025)
The study aims to investigate the inhibition efficiency of new 2-aryl imidazo[2,1-b] benzothiazole derivative namely 2- (4-bromophenyl-4-yl)-5 -yl-methylene-3- (p-tolyl)-2- phenyl- (3,5-dihydroimidazoline-4-one) imidazo [2,1-b]benz[d]thiazol (BPMDIB). Quantum chemical calculations were employed to investigate the impact of BPMDIB on carbon steel corrosion. The results showed that increasing the inhibitor concentration resulted in a substantial decrease in the corrosion rate of carbon steel, with an inhibitor efficiency value of 92% at 293 K and a concentration of 100 ppm BPMDIB. The corrosion behavior of steel in 3.5% NaCl without and with the inhibitor at different concentrations was investigated between 293 and 323 K in temperature. Potentiodynamic polarization demonstrated the mixed-type action of the inhibitor. The adsorption of BPMDIB on the surface of carbon steel was explained by the Langmuir adsorption model. Furthermore, molecular dynamics simulations and quantum chemical computations based on density functional theory were conducted to study the effect of BPMDIB on the corrosion of carbon steel and to validate the accuracy of the experimental results and determine the efficacious sites of adsorption.